HARMONI DALAM PERBEDAAN: DINAMIKA PERNIKAHAN MULTIKULTURAL TERHADAP POLA PENGASUHAN ANAK - Sekar Kirana Wulandari; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
A multicultural marriage is a marriage in which both partners have different racial, ethnic, religious, and cultural backgrounds. Parenting patterns can be said to be a parenting pattern applied by each parent in educating their children. The purpose of this study is to find out in more detail about how the differences in parenting patterns of both parents from multicultural marriages. The method used in this research is a qualitative method with data collection techniques using literature studies. The results showed that multicultural marriage is a factor in shaping parenting patterns. The results also show that parenting is closely related to culture. So, parenting patterns will be different in each family because the backgrounds brought by the parents are also different. The cultural values of the parents must be packaged into one unit to be used as a parenting pattern for their children. However, in reality, many parents choose to give in and use parenting patterns according to the times. Parenting patterns from multicultural marriages are divided into two types, namely permissive patterns and authoritative patterns.